Acute kidney injury in rural workers: An environmental-stress nephropathy - Carlos G. Musso; Gustavo Aroca-Martínez; Lil Avendaño-Echavez; Andrés Cadena-Bonfanti; Luis Castillo; Henry González-Torres; Juan C Conde; Elkin Navarro-Quiroz; William Peña-Vargas; Sandra Hernandez; María de los Ángeles Velez-Verbel; Rafael Perez; et al. (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2023)
Introduction: Mesoamerican nephropathy is a tubule-interstitial nephropathy whose etiology is still unknown. However, clinical cases like Mesoamerican nephropathy have been described in other geographically distant and ethnically diverse regions. Still, they all have a common factor: the intensity of heat and rural physical labor. Objective: To study whether this entity could occur among rural workers in a non-Mesoamerican region with similar climatic and working conditions, in the Colombian Caribbean countryside, and to consider how much repetitive dehydration could weigh in its pathogenesis.  Methodology: An observational study was carried out, based on field work in a farm in Sitio Nuevo (Colombia) with 28 rural worker volunteers (rice fields), who were measured for weight, blood pressure, and blood and urine samples to measure electrolytes and osmolarity, at 2 times of the day (morning and evening).  Results: Of the 28 young men workers evaluated, 5 (18%) presented a significant increase in serum creatinine during the day (0.8±0.15 vs 1.2±0.17, p<0.001). The volume of water ingested by the workers was highly variable (2,861 ± 1,591 cc). There was a significant increase in serum sodium (p?0.001), and urinary osmolarity (p=0.01) values between morning and afternoon values in these 5 patients.  Conclusions: Eighteen percent (18%) of the workers evaluated developed parameters compatible with acute kidney injury and dehydration during the workday in the Colombian Caribbean countryside.